A self-powered nanofiber coated yarn and its preparation method and application

By using carbon fiber wound polyurethane core yarn and PVDF-graphene spinning liquid coating technology in smart textiles, combined with pulse heating, the problem of insufficient power supply performance of self-powered textiles during large deformation movements of human joints is solved, and high output voltage is achieved and good elastic nanofiber coated yarn, suitable for complex deformation scenarios.

CN116043385BActive Publication Date: 2025-01-10SUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211599719.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-01-10
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The power supply performance and triboelectric performance of existing self-powered smart textiles in large deformation movements in human joints and other parts cannot meet the requirements, and are not suitable for complex deformation scenarios.

Method used

The polyurethane core yarn is wound with carbon fiber and formed a microporous structure through foaming, and then double-electrode electrospinning is coated with PVDF-graphene spinning liquid. Combined with pulse heating technology, nanometers with high elasticity and good self-power supply performance are prepared. Fiber coated yarn.

Benefits of technology

It realizes the generation of high output voltage during human movement, adapts to severe complex deformation, and improves the friction performance and sensitivity of fibers, satisfying the compatibility of textile technology and human comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116043385B_ABST
    Figure CN116043385B_ABST
Patent Text Reader

Abstract

The present invention relates to a self-powered nanofiber coated yarn and a preparation method and application thereof, comprising the following steps: winding carbon fiber around an outer layer of polyurethane to obtain a core yarn; immersing the core yarn in a foaming solution, taking out and pulse heating the carbon fiber to foam the polyurethane to form a core yarn with a microporous structure; mixing graphene with polyvinylidene fluoride to form a PVDF-graphene spinning solution, using the PVDF-graphene spinning solution as the positive and negative electrode spinning solution to perform double-electrode electrostatic spinning to obtain an outer yarn, coating the core yarn with a microporous structure, and pulse heating the carbon fiber after spinning until annealing of PVDF is completed. The nanofiber coated yarn prepared by the present invention has a good self-powered effect, a high energy conversion rate, and good elasticity, can adapt to the severe and complex deformation caused by human body movement, and satisfies the compatibility with textile technology and human comfort at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of textile materials, and in particular to a self-powered nanofiber coated yarn and a preparation method and application thereof. Background Art

[0002] So far, all these flexible electronic textiles developed, such as textile-based sensors, require frequent and inconvenient charging, resulting in a great waste of resources due to the lack of self-powering capabilities. Therefore, the emergence of triboelectric nanogenerator (TENG) textiles is a major breakthrough in the energy field, which can effectively harvest biomechanical energy and sense multifunctional postures and movements, and has a wide range of applications in the next generation of wearable and portable electronic devices.

[0003] At present, most of the smart textiles used for self-powered are piezoelectric effects. Lin S et al. prepared core-wrapped copper / phosphorus (PVDF-TrFE) nanofiber yarns for wearable smart textiles for monitoring human movement. The yarns were woven into breathable fabrics and integrated into clothes. The piezoelectric current generated can be detected to monitor human movement, forming self-powered smart textiles (NanoEnergy, 2020). However, piezoelectric nanogenerators are more suitable for scenes with periodic motion, such as heartbeat, breathing, wind and waves, waves, tides, etc. However, they are not suitable for sensing large deformation movements of human joints and other parts, and their power supply performance and triboelectric performance still cannot meet the requirements. For example, Fu Kun prepared a sensing fiber with a core-shell structure, in which the core is PU / CNT / Dragon Skin stretchable fiber and the outer layer is rGO / PDMS / AgNW multilayer film. But its output voltage is only 10V. Therefore, it is still necessary to find a material that can adapt to complex deformations and has good power supply function. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing self-powered nanofiber coated yarn. The obtained nanofiber coated yarn has good self-powering effect, high energy conversion rate, and good elasticity. It can adapt to the violent and complex deformation caused by human movement, while meeting the compatibility with textile technology and human comfort.

[0005] The first object of the present invention is to provide a method for preparing a self-powered nanofiber coated yarn, comprising the following steps:

[0006] S1, winding the carbon fiber around the outer layer of polyurethane to obtain a core yarn;

[0007] S2, immersing the core yarn in a foaming liquid, taking it out and pulse heating the carbon fiber to foam the polyurethane to form a core yarn with a microporous structure;

[0008] S3. Graphene is mixed with polyvinylidene fluoride to prepare PVDF-graphene spinning solution, and double-electrode electrospinning is performed using the PVDF-graphene spinning solution as the positive and negative spinning solutions to obtain outer yarn, and the core yarn with a microporous structure is coated. After spinning, the carbon fiber is pulse-heated until the annealing of the PVDF is completed to obtain the self-powered nanofiber coated yarn.

[0009] The present invention provides a self-powered nanofiber coated yarn, comprising a core yarn and an outer yarn coated on the outer surface of the core yarn, wherein the core yarn is a PU-carbon fiber obtained by spirally winding a layer of carbon fiber around the PU, and the outer yarn is a nanofiber obtained by electrostatic spinning of PVDF and graphene spinning solution. In the present invention, the carbon fiber not only plays a triple role in the preparation process, but also plays a role in triboelectric derivation in the obtained product coated yarn. Specifically, during the preparation process, the carbon fiber provides a suitable temperature for the foaming of polyurethane, and the formation of micropores on the polyurethane is beneficial to improving the elasticity of the fiber, thereby improving the piezoelectric stability and durability; secondly, the carbon fiber provides an annealing temperature for the PVDF in the outer covering yarn. Compared with the existing annealing method using heat conduction, there is no need to provide additional annealing temperature for PVDF, and the preparation method is simpler; in addition, the temperature provided by the carbon fiber is also conducive to a closer combination of the carbon fiber and PU and the carbon fiber and the outer covering PVDF, which not only improves the elasticity of the obtained self-powered nanofiber coated yarn and has good recoverability, but also makes the yarn stronger. Moreover, since the self-powered coated yarn generates piezoelectricity through PVDF and conducts piezoelectricity through the carbon fiber, the tighter combination can also improve the sensitivity of the fiber, thereby improving the friction performance of the fiber.

[0010] Furthermore, in step S2, the foaming liquid is prepared by the following steps: mixing the stearic acid-modified nano-barium carbonate with triethylenediamine and polyester polyol to form a mixed solution, and then adding diphenylmethane diisocyanate to obtain the foaming liquid.

[0011] Further, in step S2, the carbon fiber is pulse-heated to keep the temperature of the core yarn at 70-80°C to provide the temperature required for foaming.

[0012] Furthermore, in step S2, during pulse heating, the duration of each pulse is 0.2-0.25 s, and the interval time is 0.4-0.5 s.

[0013] Furthermore, in step S3, the carbon fiber is pulse-heated so that the temperature of the outer yarn is maintained at 120-135°C to provide the temperature required for annealing, thereby improving the crystallinity and mechanical properties of the PVDF-doped graphene nanofibers, making the yarn stronger and having better friction properties. During this pulse heating process, the PU bubble wall changes from solid to liquid, and there are still a large number of PU bubbles.

[0014] Furthermore, in step S3, during pulse heating, the duration of each pulse is 0.35-0.38 s, the interval time is 0.6-0.7 s, and the duration is 1-3 h.

[0015] Further, in step S3, the polyvinylidene fluoride is a β-crystalline form. The present invention selects PVDF ultrasonically doped with graphene as an efficient energy harvester for a triboelectric nanogenerator (TENG), because it is a triboelectric material with high electron affinity to prepare a triboelectric layer with an effective triboelectric area to achieve a high surface charge density. Polyvinylidene fluoride (PVDF) has five different microcrystalline polymorphs (α, β, γ, δ and ε), among which β-phase PVDF has a very promising triboelectric material for TENG due to its high piezoelectric coefficient, excellent stability and ideal flexibility.

[0016] Furthermore, in the self-powered nanofiber coated yarn, the mass ratio of polyurethane, carbon fiber, PVDF and graphene is (20-50):(30-50):(10-30):(1-4).

[0017] Further, in step S3, the concentration of graphene in the PVDF-graphene spinning solution is 1.0%-2.0%wt. Ultrasonic incorporation of carbon graphene into PVDF is very beneficial to the preferential crystallization of the β phase in PVDF, which exhibits significantly enhanced triboelectric properties to improve its surface potential and charge capture ability, thereby significantly improving the output performance of the PVDF-based TENG.

[0018] Furthermore, in the self-powered nanofiber coated yarn, the diameter of the core yarn is preferably 0.03-0.05 mm, and the thickness of the outer covering yarn is preferably 350-550 μm.

[0019] Further, in step S3, the conditions of the dual-electrode electrospinning are: voltage of ±5-15 kV; bell mouth speed of 50-250 r / min, collection roller speed of 50-120 r / min, and PVDF-graphene spinning solution injection flow rate of 1-1.2 mL / h. The thickness of the nanofiber coating layer is controlled by the rotation speed of the bell mouth in the electrospinning device and the collection speed ratio of the collection roller.

[0020] Furthermore, in step S3, the moving speed of the core yarn is 0.08-0.25 mm / s; and the angular velocity of the outer covering yarn during spiral winding is 130-170 rad / min.

[0021] Further, in step S3, graphene is incorporated into PVDF by ultrasound.

[0022] The second object of the present invention is to provide a self-powered nanofiber coated yarn prepared by the above preparation method.

[0023] The third object of the present invention is to provide the application of the self-powered nanofiber coated yarn in the field of sensing. Taking the sensing of human body movement as an example, the coated yarn of the present invention has a good self-powered effect. When the human body moves, the friction with the yarn generates a voltage. The difference in voltage can be used to show the difference in human body movement, so that the monitoring of human body movement can be realized.

[0024] The fourth object of the present invention is to provide a friction nanogenerator, which comprises the above-mentioned self-powered nanofiber coated yarn.

[0025] The fifth object of the present invention is to provide a wearable device, comprising the above-mentioned self-powered nanofiber coated yarn. The present invention uses PU with good elasticity as a raw material, and wraps a layer of carbon fiber around the elastic fiber to obtain an elastic electrode. The fiber prepared by this method has the characteristics of a stretchable electrode, which is suitable for large deformation movements of human joints and other parts, and is particularly suitable for wearable devices to ensure reliable contact between the electrode and the human skin. It has the characteristics of low power consumption, high elasticity, high strength, good flexibility, comfortable wearing, safe and reliable, and easy to use.

[0026] By means of the above scheme, the present invention has at least the following advantages:

[0027] The present invention obtains a self-powered nanofiber coated yarn with good morphology, softness and significantly enhanced triboelectric properties by improving the material matching mode and the preparation method. The coated yarn has good self-powering effect (output voltage reaches 55-78V), high energy output, good elasticity and mechanical properties (yarn breaking strength is 3276-3678CN, elongation at break is 3.8-5.4%), can adapt to the severe and complex deformation caused by human body movement, and the yarn form meets the compatibility and comfort with textile technology, which is conducive to the preparation of smart wearable fabrics.

[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments of the present invention in conjunction with the accompanying drawings.

[0030] Figure 1 It is a schematic diagram of a process flow of a method for preparing a self-powered nanofiber coated yarn;

[0031] Figure 2 It is a schematic diagram of the structure of self-powered nanofiber-coated yarn carbon fiber spirally coated;

[0032] Figure 3 This is a schematic diagram of the structure of the nanofiber-coated yarn carbon fiber parallel coating in Comparative Example 2;

[0033] Figure 4 It is a scanning electron microscope photo of the self-powered nanofiber coated yarn; among them, (a) is a cross-sectional view of the self-powered nanofiber coated yarn, (b) is the core foamed PU layer, and (c) is a local view of the foaming.

[0034] Description of reference numerals:

[0035] 1. Negative electrode; 2. Positive electrode; 3. Nanofiber coated yarn; 4. PVDF-graphene spinning solution; 5. Nanofiber; 6. Conical surface; 7. Bell mouth; 8. Core yarn; 9. Winding roller; 301. Polyurethane; 302. Outer layer; 303. Carbon fiber. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0037] Example 1

[0038] A method for preparing a self-powered nanofiber coated yarn comprises the following steps:

[0039] (1) The core yarn is made of polyurethane (PU) with a linear density of 20D, and a layer of carbon fiber is spirally wrapped around the PU outer layer to obtain PU-carbon fiber;

[0040] (2) PU-carbon fiber is immersed in a foaming liquid to prepare PU with micropores. First, the surface of nano-BaCO3 is modified with stearic acid. Then, it is mixed with triethylenediamine and added to polyester polyol to form a mixed solution. After high-speed mixing, it is allowed to stand. Finally, it is quickly mixed with diphenylmethane diisocyanate at 75-80°C. The core yarn prepared above is immersed in the foaming liquid to allow the PU to foam freely to form a PU with micropores. The temperature required for PU foaming is controlled by heating the carbon fiber. That is, the core yarn is taken out of the foaming liquid and the carbon fiber is pulse-heated. The time of each pulse is 0.2-0.25s, the interval time is 0.4-0.5s, and the heating is 1h.

[0041] (3) PVDF-graphene spinning solution was prepared by solution blending method, graphene nanosheets were ultrasonically dispersed in DMF for 0.5 h, and then PVDF powder was dissolved in DMF solution at 60 °C and heated in a water bath, and stirred with a magnetic stirrer for 6 h to obtain graphene-PVDF spinning solution, in which the mass fraction of graphene was 1.0% and the mass fraction of PVDF was 15%.

[0042] (4) The PU-carbon fiber after foaming is used as the core yarn, and the PVDF-graphene spinning solution is divided into two equal parts as the positive and negative electrospinning solutions respectively. The dual-electrode electrospinning technology is used to adjust the electrospinning parameters, and the PU-carbon fiber is rotationally coated by a conventional nozzle-type electrospinning device to obtain nanofiber coated yarn; the conditions of the dual-electrode electrospinning include: voltage of ±10kV; bell mouth speed of 125r / min, collection roller speed of 95r / min; the injection flow rate of the positive electrospinning solution and the negative electrospinning solution is 1mL / h; the distance between the syringe needle and the aluminum foil collector is fixed at 15cm; the temperature is maintained at 25°C; and the relative humidity is controlled at about 40%.

[0043] The mass ratio of the nanofiber coated yarn is polyurethane (PU): carbon fiber: PVDF: graphene is 20:30:30:2. The thickness of the nanofiber coating layer is 350 μm.

[0044] (5) After the electrospinning is completed, the carbon fiber is pulsed and heated. Each pulse lasts for 0.35-0.38 seconds and the interval is 0.6-0.7 seconds. The temperature is raised to 130-135°C for two hours to complete the annealing of PVDF. The obtained nanofiber-coated yarn is a single-electrode friction nanogenerator (TENG).

[0045] Example 2

[0046] A method for preparing a self-powered nanofiber coated yarn comprises the following steps:

[0047] (1) The core yarn is made of polyurethane (PU) with a linear density of 30D, and a layer of carbon fiber is spirally wound around the PU outer layer to obtain PU-carbon fiber;

[0048] (2) The PU-carbon fiber is immersed in a foaming liquid to prepare a PU with micropores. The foaming process and the heating process are the same as those in Example 1, except that the foaming temperature is controlled to be 70-75°C.

[0049] (3) PVDF-graphene spinning solution was prepared by solution blending method, graphene nanosheets were ultrasonically dispersed in DMF for 0.5 h, and then PVDF powder was dissolved in DMF solution at 60 °C and heated in a water bath, and stirred with a magnetic stirrer for 6 h to obtain graphene-PVDF spinning solution, in which the mass fraction of graphene was 1.5% and the mass fraction of PVDF was 15%.

[0050] (4) The PU-carbon fiber after foaming is used as the core yarn, and the PVDF-graphene spinning solution is divided into two equal parts as the positive and negative electrospinning solutions respectively. The dual-electrode electrospinning technology is used to adjust the electrospinning parameters, and the PU-carbon fiber is rotationally coated by a conventional nozzle-type electrospinning device to obtain nanofiber coated yarn; the conditions of the dual-electrode electrospinning include: voltage of ±8kV; bell mouth speed of 110r / min, collection roller speed of 85r / min; the injection flow rate of the positive electrospinning solution and the negative electrospinning solution is 1.1mL / h; the distance between the syringe needle and the aluminum foil collector is fixed at 15cm; the temperature is maintained at 25°C; and the relative humidity is controlled at about 40%.

[0051] The mass ratio of the nanofiber coated yarn is polyurethane (PU): carbon fiber: PVDF-graphene is 20:30:30:3. The thickness of the nanofiber coating layer is 450 μm.

[0052] (5) After the electrospinning is completed, the carbon fiber is pulse heated to raise the temperature to 125-130°C for 2.5 hours to complete the annealing of the PVDF.

[0053] The electron microscope image of the nanofiber coated yarn prepared in this example is shown in Figure 4 As can be seen from the figure, the outer layer of carbon fiber is wrapped with a layer of PVDF, and the core layer of PU is a porous foam structure.

[0054] Example 3

[0055] A method for preparing a self-powered nanofiber coated yarn comprises the following steps:

[0056] (1) The core yarn is made of polyurethane (PU) with a linear density of 40D, and a layer of carbon fiber is spirally wound around the PU outer layer to obtain PU-carbon fiber;

[0057] (2) The PU-carbon fiber is immersed in a foaming liquid to prepare a PU with micropores. The foaming process and the heating process are the same as those in Example 1.

[0058] (3) PVDF-graphene spinning solution was prepared by solution blending method, graphene nanosheets were ultrasonically dispersed in DMF for 0.5 h, and then PVDF powder was dissolved in DMF solution at 60°C and heated in a water bath, and stirred with a magnetic stirrer for 6 h to obtain graphene-PVDF spinning solution, in which the mass fraction of graphene was 2.0% and the mass fraction of PVDF was 15%.

[0059] (4) The PU-carbon fiber after foaming is used as the core yarn, and the PVDF-graphene spinning solution is divided into two equal parts as the positive and negative electrospinning solutions respectively. The dual-electrode electrospinning technology is used to adjust the electrospinning parameters, and the PU-carbon fiber is rotationally coated by a conventional nozzle-type electrospinning device to obtain nanofiber coated yarn; the conditions of the dual-electrode electrospinning include: voltage of ±15kV; bell mouth speed of 100r / min, collection roller speed of 75r / min; the injection flow rate of the positive electrospinning solution and the negative electrospinning solution is 1.2mL / h; the distance between the syringe needle and the aluminum foil collector is fixed at 15cm; the temperature is maintained at 25°C; and the relative humidity is controlled at about 40%.

[0060] The mass ratio of the nanofiber coated yarn is polyurethane (PU): carbon fiber: PVDF: graphene is 20:30:30:4. The thickness of the nanofiber coating layer is 550 μm.

[0061] (5) After the electrospinning is completed, the carbon fiber is pulse heated, with each pulse lasting 0.35-0.38 s and an interval of 0.6-0.7 s, to raise the temperature to 130-135 °C for two hours to complete the annealing of the PVDF.

[0062] Example 4

[0063] The specific operation steps are the same as those in Example 2, except that the mass ratio of the nanofiber coated yarn in this example, polyurethane (PU): carbon fiber: PVDF: graphene, is 50:30:10:1.

[0064] Example 5

[0065] The specific operation steps are the same as those in Example 2, except that the mass ratio of the nanofiber coated yarn in this example, polyurethane (PU): carbon fiber: PVDF: graphene, is 20:50:20:1.

[0066] Comparative Example 1

[0067] The specific operation steps are the same as those in Example 2, except that the outer carbon fibers of the core yarn are not spirally wound but are parallelly wrapped.

[0068] Comparative Example 2

[0069] The specific operation steps are the same as those in Example 2, except that the foaming step of step (2) is not included.

[0070] Comparative Example 3

[0071] The specific operation steps are the same as those in Example 2, except that the annealing of PVDF is not performed by pulse heating of carbon fiber, but by heat conduction heating in an oven (the oven temperature is the same as the carbon fiber heating temperature in Example 2).

[0072] Comparative Example 4

[0073] The specific operation steps are the same as those in Example 2, except that: in this example, fiber membrane is prepared instead of coated yarn, and the thickness of the coating layer is 450 μm.

[0074] Test Case

[0075] (1) The electrical output performance of the coated yarns of Examples 1-5 and Comparative Examples 1-4 was tested, and the specific experimental process is as follows.

[0076] For the electrical output test of the yarn, both ends of the yarn are fixed on paper for testing. Unless otherwise specified, the test length of the yarn used in this section is 25 cm. In the test environment of 55% air humidity and 22°C room temperature, the friction nanogenerator wrapped with yarn is fixed on the baffle, and the acrylic plate is fixed on one end of the linear motor. By setting the moving acceleration of the linear motor, the contact and separation frequency of the friction nanogenerator on the acrylic plate and the baffle is controlled. The core yarn of the nanogenerator is connected to the test end of the Keithley 6514 electrometer, and the output voltage of the test yarn is recorded using the electrometer (Keithley6514). The mechanical movement of the standard test is controlled by a linear motor (LinMotE1100).

[0077] Table 1 Electrical output properties of different nanofiber coated yarns

[0078]

[0079] The results show that: a layer of carbon fiber is spirally wrapped around the core yarn, and the carbon fiber is heated by voltage. By pulse heating to about 135°C, the carbon fiber is electrified to complete the annealing of PVDF, improve the crystallinity of PVDF, improve the firmness of PVDF on the surface of the core yarn, and improve the triboelectric properties of PVDF fibers. Within a certain thickness range, as the thickness increases, the electrical output performance of the yarn continues to increase, but beyond this range, the performance may remain unchanged or even decrease, mainly because the electrodes of the yarn are too small.

[0080] (2) The tensile mechanical properties of Examples 1-5 and Comparative Examples 1-4 were tested, and the specific experimental process is as follows.

[0081] A single fiber strength tester, an electronic single yarn strength tester or a yarn strength and elongation tester is used to test the tensile and fracture properties of the nanofiber coated yarn. At this time, the pre-drafting multiple of the nanofiber coated yarn is set to 3.5, the twist is 470T / m, and the yarn density is 78dtex as a constant. The breaking strength and elongation at break of the nanofiber are measured. Subsequently, the coated yarn spun by a hollow spindle coating machine is used as the test object. After the spun yarn is balanced under standard conditions for 48 hours, the tensile properties of the coated yarn are tested.

[0082] Table 2 Tensile mechanical properties test results

[0083] sample Breaking strength (CN) Elongation at break (%) Example 1 3276 3.9 Example 2 3465 4.4 Example 3 3398 4.1 Example 4 3470 5.4 Example 5 3678 3.8 Comparative Example 1 2765 1.6 Comparative Example 2 2824 1.8 Comparative Example 3 3329 2.1 Comparative Example 4 3392 1.4

[0084] Because the degree of coating is closely related to heating temperature rise, if the outer carbon fiber of the core yarn is parallel coated, the temperature rise of the carbon fiber is slow in the process of heating the carbon fiber by voltage in Comparative Example 1 to complete the annealing of PVDF, so the crystallinity of PVDF is improved slowly, and the triboelectric performance of PVDF fiber is improved slowly. Through the test of the electrical output performance of the coated yarn, it is found that the output voltage of the nanofiber coated yarn will also decrease. Through the tensile mechanical performance test, it is found that the elongation at break of Comparative Example 1 is very small, so the spiral coating of the outer carbon fiber of the core yarn can improve the elasticity of the yarn to a certain extent, and the tensile performance is better.

[0085] As can be seen from the table, the mass ratio of polyurethane (PU): carbon fiber: PVDF: graphene in Example 2 nanofiber coated yarn is 20:30:30:3, and the thickness of the nanofiber coating layer is 450μm. At this time, the output voltage of the nanofiber coated yarn is the highest, and the mass ratio of PVDF in the nanofiber outer layer is the highest. Because the preferential crystallization of the β phase in PVDF is very beneficial, it has significantly enhanced triboelectric properties to improve its surface potential and charge capture ability. Therefore, the output voltage of the nanofiber coated yarn is the highest at this time, so the output performance of the PVDF-based TENG can be significantly improved. Example 4 The mass ratio of polyurethane (PU): carbon fiber: PVDF: graphene in the nanofiber coated yarn is 50:30:10:1, and the stretchability of the nanofiber coated yarn is the highest. Example 5 The mass ratio of polyurethane (PU): carbon fiber: PVDF: graphene in the nanofiber coated yarn is 20:50:20:1, and the mechanical properties of the nanofiber coated yarn are the best. Comparative Example 3 is a fiber membrane with the worst tensile properties. Since the polyurethane in Comparative Example 2 is not foamed and has no micropores, the coated yarn has poor elasticity, poor recoverability, and low output voltage.

[0086] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a self-powered nanofiber coated yarn, characterized in that: The following steps are involved: S1, winding the carbon fiber around the outer layer of polyurethane to obtain a core yarn; S2, immersing the core yarn in a foaming liquid, taking it out and pulse heating the carbon fiber to foam the polyurethane to form a core yarn with a microporous structure; S3, mixing graphene and polyvinylidene fluoride to prepare PVDF-graphene spinning solution, using the PVDF-graphene spinning solution as the positive and negative spinning solutions for double-electrode electrospinning to obtain outer yarn, coating the core yarn with a microporous structure, and after spinning, pulse heating the carbon fiber until the annealing of the PVDF is completed to obtain the self-powered nanofiber coated yarn; The carbon fiber is pulse heated so that the temperature of the core yarn is maintained at 70-80°C, and the carbon fiber is pulse heated so that the temperature of the outer yarn is maintained at 120-135°C. In the self-powered nanofiber coated yarn, the mass ratio of polyurethane, carbon fiber, PVDF and graphene is (20-50): (30-50): (10-30): (1-4).

2. The preparation method according to claim 1, characterized in that: In step S3, the polyvinylidene fluoride is in β-crystal form.

3. The preparation method according to claim 1, characterized in that: In step S2, the foaming liquid is obtained by mixing stearic acid-modified nano-barium carbonate with triethylenediamine and polyester polyol to form a mixed solution, and then adding diphenylmethane diisocyanate.

4. The self-powered nanofiber coated yarn prepared by the preparation method according to any one of claims 1 to 3.

5. Application of the self-powered nanofiber coated yarn as described in claim 4 in the field of sensing.

6. A triboelectric nanogenerator, characterized in that: The friction nanogenerator comprises the self-powered nanofiber coated yarn as described in claim 4.

7. A wearable device, characterized in that: The wearable device comprises the self-powered nanofiber coated yarn of claim 4.

Citation Information

Patent Citations

  • A flexible supercapacitor and a preparation method thereof

    CN109192538A

  • Preparation method and application of microporous conversion alloying material

    CN114864892A

  • Wrap yarn

    CN206033973U